Geological-engineering integrated reconnaissance survey technology for skylights as a hidden disaster-causing factor - Mintao DONG (Meitian dizhi yu kantan)
ObjectiveSkylights represent a primary hidden disaster factor in mines in the southern Yushen mining area within the Shanbei Jurassic coalfield, Shaanxi Province. Since they are hidden and difficult to detect, their distribution in the mining area remains unclear, posing pronounced safety hazards. This necessitates developing effective technical means to overcome challenges in the spatial exploration of skylights and ensure mine safety. MethodsFocusing on a typical mine in the Yushen mining area as an example, this study explored the spatial distribution characteristics and types of skylights in the study area using the geological-engineering integrated reconnaissance survey technology that combines geological analysis, scientific assessment, and engineering exploration. Results and conclusions The results indicate that the formation and evolution of skylights in the study area are primarily governed by the paleochannels, while also exhibiting some inheritance from modern rivers. The high-density direct current electric method and micromotion exploration yielded distinct resistivity and acoustic signals of skylights in the study area, exhibiting significantly high resistivity and anomalous wave velocities. In contrast, the transient electromagnetic method yielded insignificant responses of physical properties. The developmental areas of skylights consist of lithologic assemblages formed by paleochannel sediments, exhibiting a distinct dual structure and lithologic assemblage characteristics of secondarily deposited laterites mixed or interbedded with sandy soil layers in channels. The developmental areas of laterites are characterized by borehole shrinkage, small fluid leakage in boreholes, and upright rock layers with distinct stratification. In the developmental areas of skylights, loess and laterites exhibit permeability coefficients of 2.21×10−2 m/d and 7.18×10−3 m/d, respectively, suggesting that laterites have a higher capacity to block water flow than loess. Comprehensive geophysical prospecting allows for the quick identification of anomalous laterite areas on a horizontal plane, providing a basis for accurately delineating skylights using detailed exploration engineering. Concurrently, the detailed exploration results can verify the accuracy of the resistivity and acoustic signal characteristics of skylights derived using comprehensive geophysical prospecting. The results of this study can provide technical support for the reconnaissance survey and treatment of the skylights formed by the lacuna of laterites in the study area and serve as a guide of technical means for the effective exploration of skylights in mining areas with geological conditions similar to those in the study area, thus offering geological guarantee technology for safe, efficient, green, and intelligent coal mining.